On the Educational Value of Technology in the 21st Century - Zhuang, Yinxia (International Journal of Management and Education in Human Development, 2022)
Starting from the requirements of human development in the 21st century, countries around the world have reached a broad consensus that 21st-century skills with high-order thinking ability as the core are the purpose of current education. From the perspective of technology as a field for human beings to gain freedom and liberation, technology for the development of higher-order thinking ability enables people to obtain the freedom and liberation of the right to exert their own creativity. This kind of educational value that aims to make people become the masters of the future society and have the ability to actively transform society demonstrates the meta-value of education. Throughout the ages, technology has always played an intermediary role in educational activities. In the 21st century's educational activities, technology should become the medium of education's meta-value.